Nuchal Translucency in Normal Fetus and Its Variation With Increasing Crown Rump Length (Crl) and Gestational Age - Karki, S; Joshi, KS; Tamrakar, SR; Regmi, S; Khanal, K (Kathmandu University Medical Journal, 2015)
Background Nuchal translucency (NT) is the fluid collection behind the fetal neck which can be measured by ultrasound at 11-14 weeks of gestation. Increase in the nuchal translucency thickness is associated with various congenital anomalies. Objective To study the relationship between nuchal translucency thickness, crown rump length and gestational age in normal fetus. Methods Prospective analytical study conducted on 211 pregnant women from March 2011 to August 2012. Measurement of Nuchal translucency thickness and crown rump length was performed by ultrasound at 11-14 weeks of gestation. The relationship between nuchal translucency thickness, crown rump length and gestational age was studied by using linear regression analysis. Results The mean CRL was 63.67+13.48mm (range 41.2-88mm) and mean NT thickness was 1.55+0.35mm (range 0.8-2.7mm), respectively. The median gestational age was 12.9 weeks. The regression equation which shows relation between median NT thickness and CRL was described as follows: expected NT thickness = 0.013CRL+0.725, (R2 = 0.258, p <0.001). There was increase in the incidence of NT thickness more than or equal to 2.5mm; 1.7% in fetus between 12-12.9 weeks of gestation to 15.1% in fetus between 14.0-14.9 weeks. Conclusion Our study offers normative data of NT thickness in normal fetus, which can be used as reference to screen various chromosomal and congenital abnormalities between 11- 14 weeks of gestation. NT thickness increased with increasing CRL and a false positive rate increases with increasing gestational age. Kathmandu Univ Med J 2013; 11(4): 282-286